The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Vital Dyes in Vitreoretinal Surgery 2008
DOI: 10.1159/000138988
|View full text |Cite
|
Sign up to set email alerts
|

Trityl Dyes Patent Blue V and Brilliant Blue G – Clinical Relevance and in vitro Analysis of the Function of the Outer Blood-Retinal Barrier

Abstract: The use of vital dyes during vitrectomy allows easier removal of less recognizable structures like epiretinal membranes or the internal limiting membrane (ILM). In recent years, numerous studies have investigated the use of indocyanine green (ICG), trypan blue (Membrane Blue), triamcinolone, autologous blood and presently trityl dyes such as patent blue V (PBV, Blueron), crystal violet and brilliant blue G (BBG, Brilliant Peel) in chromovitrectomy. Reports on potential risks of these dyes, especially ICG, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
(40 reference statements)
0
8
0
2
Order By: Relevance
“…Compared with previous experiments in RPE and neuronal cell culture, for instance by Mennel et al, our study found a similar safety for BriB at two doses. 34 Usually research in animals is considered better evidence of pharmacological activity than cell culture alone, since it may better simulate the actual human retinal environment. However, there are interspecies variations which may produce results that may not be translated to human experience in chromovitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous experiments in RPE and neuronal cell culture, for instance by Mennel et al, our study found a similar safety for BriB at two doses. 34 Usually research in animals is considered better evidence of pharmacological activity than cell culture alone, since it may better simulate the actual human retinal environment. However, there are interspecies variations which may produce results that may not be translated to human experience in chromovitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other cell culture models, such as the human RPE cell line ARPE-19 [7,8,9,10], retinal ganglion cells [11] and human primary RPE cells [12,13], the HFRPE culture model shows a robust cell culture to exhibit the morphology and physiology of healthy RPE in vivo [14,15]. It is a useful model to test the effect of novel vital dyes on outer BRB function before clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising new stain appears to be brilliant blue G, which has a high affinity for the ILM, is less invasive, has a good biocompatibility, and is easy to handle [37][38][39][40][41]. In vitro on ARPE-19 cell lines, however, brilliant blue G was less promising, as it demonstrated toxicity at short exposure times [42], while ICG had a favorable viability profile.…”
Section: Discussionmentioning
confidence: 99%